The case for a Martian origin of the shergottites - Nitrogen and noble gases in EETA 79001 - Becker, R. H.; Pepin, R. O. (1984)
Nitrogen and noble gases have been measured in samples of a glass inclusion and its surrounding basaltic matrix in an Antarctic shergottite meteorite (EETA 79001). The nitrogen component was found trapped in the glass, but not the matrix, having a value of delta 15-N = +190 per mil. Ratios between abundances of Ar-40 and N-14, N-15 and N-14 in the glass are consistent with the dilution of a Martian atmospheric component. The trapped noble gases in the glass are similar to elemental and isotopic compositions measured in Mars atmosphere by the Viking lander, and are in general agreement with previous measurements. It is suggested that a sample of Martian atmosphere has been caught in the EETA 79001 glass, and that other shergottite, nakhilite, and chassignite meteorites with similar features probably also originated on Mars. A table is presented which lists the abundances of nitrogen and the noble gases found in the non-glassy matrix and in the EETA 79001 glass.